High resolution optical satellite imagery - Dowman, Ian J.; Jacobsen, Karsten; Konecny, Gottfried; Sandau, Rainer (Whittles Publishing, 2012)
This is a comprehensive guide to the characteristics and use of high resolution optical images from satellite-borne sensors, concentrating on sensors designed for mapping. It considers the SPOT series of satellited and sensors with a ground sample distance (GSD) of less than 15m, operational since SPOT 1.
Keywords: Remote-sensing images.; Satellite geodesy.; elektronické knihy; electronic books